Rasio Efektivitas Biaya Obat Antimalaria Kombinasi Artesunat Amodiakuin dan Kombinasi Sulfadoksin Pirimethamin Dalam Terapi Malaria Falsiparum di Sumba - DELINA HASAN; ASCOBAT GANI; PURWANTYASTUTI PURWANTYASTUTI; INGE SUTANTO (JURNAL ILMU KEFARMASIAN INDONESIA, 2013)
Malaria cases continue to increase in Indonesia, and one of the causes is many malaria parasites resistant to antimalarial drugs such as chloroquine and sulfadoxine pyrimethamine. Antimalarial drug combination recommended by the WHO yet widely available. This study aimed to explore alternative antimalarial drugs through examination of drug-effectiveness and cost-effectiveness analysis of antimalarial drug combination artesunate amodiaquine and sulfadoxine pyrimethamine. To assess the effectix eness or antimalarial drug combinations, as many asl64 patients with who meet inclusion and exclusion criteria were divided into 2 groups with 82 patients respectively. First group was given artesunate amodiaquine while the second group was given sulfadoxine pyrimethamine, and observed for 14 to 28 days. Responses to treatment according to the WHO protocol to include clinical response and parasitological response. The cost effectiveness was assessed through the pharmacoeconomic evaluation method. The results showed that fever clearence time and parasites clearence time by the artesunate amodiaquine combination was faster than by sulfadoxine pyrimethamine combination, and the cost effectiveness ratio of artesunate amodiaquine combination was lower than of sulfadoxine pyrimethamine. In conclusion, the antimalarial drug artesunate amodiaquine combination was more effective and more eflicient than the sulfadoxin pyrimethamine combination, and its cost effectiveness ratio was lower than the sulfadoxine pyrimethamine combination (p=0.05).